(untitled) (Annals of Medical Research, 2021)
Aim: In colorectal cancer (CRC), expression of genes involved in the PI3K/Akt signaling pathway varies significantly. Studies have shown that microRNAs (miRNA) have important roles in the development of CRC. Accordingly, the aim of this study was to determine miRNAs affecting the critical genes in the PI3K/Akt pathway by analysis of The Cancer Genome Atlas (TCGA) CRC data sets and to evaluate the clinical significance of these miRNAs. Material and Methods: Initially, CRC mRNA, miRNA expression levels and patient data were obtained from TCGA database. The study included 220 CRC patients. MiRNAs that were negatively correlated with genes in the PI3K/Akt signaling pathway were selected, and their expression levels were compared with the clinical and demographic characteristics of CRC patients.Results: miR-18a, miR-19b, miR-17, miR-106b, miR-130b and miR-135b were found to be negatively correlated with genes that play key roles in the PI3K/Akt pathway. Also, miR-18a, miR-19b, miR-17 and miR-135b were found to vary significantly according to the CRC subtype.Conclusion: Consequently, the PI3K/Akt signaling pathway was found to be deregulated in CRC and the majority of genes involved in this signaling pathway were associated with miRNAs. Thus, PI3K/Akt miRNA axis might serve as a potentially distinctive diagnostic, prognostic and therapeutic avenue against CRC.